Ukrainian Women’s Entrepreneurship and Business Ecosystem during the War: New Challenges for Development. - Stroiko, Tetiana; Iglesias-Sánchez, Patricia Pilar; Jambrino-Maldonado, Carmen; Fernández-Díaz, Elena; De-las-Heras-Pedrosa, Carlos (MDPI, 2024)
This research focuses on the key aspects of the basis of women’s entrepreneurship in the particular case of the Ukrainian ecosystem of entrepreneurship. Even in wartime, entrepreneurship is a chance to overcome circumstances, and it should be developed for women and men. A correla- tion regression analysis and simulation modeling were carried out in order to rank the priorities for the development of types of economic activity of small business entities managed by women, mak- ing it possible to substantiate the forecast of the development of women’s entrepreneurship in Ukraine for 2024–2026. The findings show the positive impact of the entrepreneurial ecosystem and the need to continue to strengthen policies that encourage and facilitate female entrepreneurship. This analysis provides three types of development scenarios for women’s entrepreneurship in Ukraine.
Keywords: Mujeres en el desarrollo; Empresarias - Ucrania; Guerra de Ucrania, 2022 - Aspectos económicos; Entrepreneurship; Women’s entrepreneurship; Barriers/non-barriers for women’s entrepreneurship